CHANGE OF SOIL CHEMICAL PROPERTIES AMENDED WITH SAGO WASTE AND THE YIELD OF MUNG BEAN IN INCEPTISOL - Darwis Suleman; Namriah; Syamsu Alam; Muhammad Algifari (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2022)
[CHANGES IN SOIL CHEMICAL PROPERTIES AND MUNG BEAN (Vigna radiata L.) YIELD IN INCEPTISOLS, NORTH MORAMO AS AFFECTED BY APPLICATION OF SAGO WASTE COMPOST]. Inceptisols are one of the most widespread soil types in Southeast Sulawesi with an acreage of ​​around 2,280,567 ha (62.07%) and potential for agriculture development. The primary drawback of Inceptisols developed for cultivating mung bean includes a highly acid soil reaction with low soil pH. The polybag experiment was conducted with the objective to determine changes in the chemical properties of the soil after being amended with sago waste compost and its effects on mung bean yield. The research was conducted at the Experimental Garden of the Faculty of Agriculture, Halu Oleo University. This study used a randomized block design consisting of five levels of sago pulp compost (i.e., 0, 100, 200, 300, and 400 g/polybag) with three replications. The results showed that the application of 400 g/polybag of sago pulp compost increased soil pH and organic C by 5.02 and 2.23%, respectively. Increases were also observed in total-N (0.24%), available-P (19.85 ppm), available-K (0.24 me/100g), and CEC (11.99 me/100g). The application of 300 g/polybag of sago pulp compost resulted in the highest number of pods (11.33 pods) and the weight of 100 green bean seeds (9.39 g).